2020
DOI: 10.1111/ans.15659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise prehabilitation on functional status of patients undergoing bowel resection: a systematic review

Abstract: Background: Bowel resections have high morbidity and mortality rates and are becoming increasingly common in Australia. To reduce the burden on patients and the health system, measures for improving patient outcomes after resection must be investigated. One possible method for improving patient outcomes is prehabilitation with exercise. The aim of this systematic review is to determine the effect that exercise prehabilitation has on the functional status of patients undergoing colorectal resection. Method: Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…The evaluation and selection of patients at risk of poor postoperative physical activity and postoperative complications could permit to target special management to these patients and increase compliance to preoperative exercises. Recently, some reviews showed that prehabilitation improved significantly functional capacity and self-reported physical activity but the impact on postoperative complications was limited [19]. Furthermore, a recent randomized trial has shown that a multimodal prehabilitation program did not affect postoperative outcomes in frail patients undergoing colorectal cancer resection [20].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation and selection of patients at risk of poor postoperative physical activity and postoperative complications could permit to target special management to these patients and increase compliance to preoperative exercises. Recently, some reviews showed that prehabilitation improved significantly functional capacity and self-reported physical activity but the impact on postoperative complications was limited [19]. Furthermore, a recent randomized trial has shown that a multimodal prehabilitation program did not affect postoperative outcomes in frail patients undergoing colorectal cancer resection [20].…”
Section: Discussionmentioning
confidence: 99%
“…11 Their RCT was followed by a large number of primary studies whose results have been synthesised in various systematic reviews, the majority of which looked at abdominal surgery. [12][13][14][15][16][17][18][19][20][21][22] The cost-effectiveness of an intervention, that is, its value for money, is an important factor for health policymakers deciding about the implementation of a new programme. 23 However, despite the growing interest in prehabilitation programmes by healthcare professionals and policy-makers, only a subset of studies has evaluated the cost-effectiveness of prehabilitation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…8 However, there are few reports on whether preoperative exercise in improving effectively intestinal function through systematic literature retrieval. 9,10 Therefore, in this study, the preoperative walking protocol is appilied to patients with gynecological malignancy who plan laparoscopic surgery to explore the impact on the recovery of postoperative intestinal function, in order to provide clinical reference.…”
Section: Introductionmentioning
confidence: 99%